Literature Study Of Factors Affecting Hand Washing Behavior In Pre-Age Children School - pinantika, kuwandaning (Journal of Global Research in Public Health, 2022)
Nowadays, hand washing behavior has not become a culture or habit that is applied in everyday life, especially in school and preschool age children. Factors that influence children's behavior in washing hands are age, gender, environment, parental roles, and information (Kustiyah, 2015). The method in searching for article data sources is carried out through the pubmed, google schoolar and garuda databases (2015-2020) to retrieve relevant articles published in English and Indonesian. Search articles or journals using keywords and boolean operators (AND, OR NOT or AND NOT) which are used to expand or specify the search, making it easier to determine the articles or journals used. The keywords used in this study are hand washing behavior and preschool children. Literature Review is focused on original non-experimental research types, where research articles contain the results of actual observations where there are abstracts, introductions, methods, results, and discussions so that 5 journals are reviewed. The results of 5 journals reviewed, almost half (40%) stated that parenting is a factor that influences hand washing behavior in preschool children, and another small part is influenced by parental support, working mother behavior and mother's level of knowledge with a total 20% each. Based on a literature review of 5 research journals, it can be concluded that the factors that influence the behavior of preschool children in washing their hands include parental support, level of parental knowledge, behavior of working mothers and parenting patterns.